PROFICIENCY LEVEL AND LANGUAGE LEARNING STRATEGIES AMONG JORDANIAN STUDENTS AT UNIVERSITI UTARA MALAYSIA - Eshraq Mahmoud Mustafa Jaradat; Haryati Bakrin (Proceedings of The ICECRS, 2016)
This study examines the relationship between proficiency level and language learning strategies (LLSs) among Jordanian students enrolled at Universiti Utara Malaysia. The frequency level of the LLSs employed by the students was also investigated. The theoretical foundation for the study was provided by three comprehensive theories which are the Behaviorism, the Cognitive Psychology, and the Schema Theory. The data for the LLSs was obtained from using Oxford’s (1990) Strategy Inventory for Language Learning (SILL) that classifies six different strategies: 1) Memory Strategy (MS), (2) Cognitive Strategy (COG), (3) Compensation Strategy (COMPS), (4) Metacognitive Strategies (MET), (5) Affective Strategy (AFCS) and (6) Social Strategies (SOC). The frequency of the students’ overall use of LLSs was determined on a five-point Likert scale, ranging from high frequency use (3.5-5.0), medium frequency use (2.5-3.49), to low frequency use (1.0-2.49). Questionnaires were distributed and collected from a total of 97 students. Meanwhile, the students’ level of language proficiency was determined by their scores in the UUM English Language Proficiency Test (ELPT). Upon using the multiple regression analysis, the results show that the students used language learning strategies at a high frequency level. In addition, this study shows that there is a positive relationship between language learning strategy and proficiency level. These results indicate that proficiency level plays a vital role in determining the kinds of language learning strategy used. Curriculum designers and related bodies in Jordan should increase focus on the role of language learning strategies in promoting the acquisition of English language proficiency. The study also opens up avenues for more studies on language learning strategies not only in Jordan, but also in other countries where this area of study is lacking.